1987
DOI: 10.1111/j.1476-5381.1987.tb11272.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term imipramine treatment enhances locomotor and food intake suppressant effects of m‐chlorophenylpiperazine in rats

Abstract: 1 Administration of the 5-HTIB receptor agonist m-chlorophenylpiperazine (m-CPP) to rats produces dose-dependent decreases in locomotor activity and food intake. 2 The locomotor suppressant effect of m-CPP was inhibited by the 5-hydroxytryptaminergic antagonist, metergoline, but not by phentolamine, propranolol, clonidine, or haloperidol. 4 The food intake suppressant effects of m-CPP were enhanced following both short (3-5 days) and longer-term (21 days) treatment with imipramine. Rapidly developing 5-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Similarly, the m-trifluoromethyl-phenylpiperazine (TFMPP) stimulus in drug discrimination studies does not generalize to the 5-HT1A agonist, 8-OHDPAT, or to the putative 5-HT2 agonist, 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), but does generalize to agents such as m-CPP and 5-methoxy-3-(l,2,3,6-tetrahydro-pyridin-4-yl)-lH-indole (RU24969) that display a high affinity for 5-HT1B sites (McKenney and Glennon 1986). Administration of m-CPP to rats produces dose-dependent reductions in food intake and locomotor activity; these effects are attenuated by pretreatment with the 5-HT receptor antagonist, metergoline (Samanin et al 1979;Aulakh et al 1987).…”
mentioning
confidence: 94%
“…Similarly, the m-trifluoromethyl-phenylpiperazine (TFMPP) stimulus in drug discrimination studies does not generalize to the 5-HT1A agonist, 8-OHDPAT, or to the putative 5-HT2 agonist, 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), but does generalize to agents such as m-CPP and 5-methoxy-3-(l,2,3,6-tetrahydro-pyridin-4-yl)-lH-indole (RU24969) that display a high affinity for 5-HT1B sites (McKenney and Glennon 1986). Administration of m-CPP to rats produces dose-dependent reductions in food intake and locomotor activity; these effects are attenuated by pretreatment with the 5-HT receptor antagonist, metergoline (Samanin et al 1979;Aulakh et al 1987).…”
mentioning
confidence: 94%
“…These data support our previous results indicating that the effects of m-CPPand 8-OHDPAT are mediated by different mechanisms. Earlier studies demonstrated that metergoline pretreatment attenuates the effects of m-CPP on food intake, locomotor activity, plasma PRL, and CAs [4,6,7,43,45). Simi larly, metergoline pretreatment decreases plasma PRL re sponses to 8-OHDPAT [5].…”
mentioning
confidence: 99%
“…It also has higher affinity for 5-HTm than 5-HTia receptors [3,49], although other studies [23, 26] found m-CPP to have almost equal affinity for 5-HTia versus 5-HTm sites. m-CPP increases plasma prolactin (PRL) [2,7, 38,43] and catecholamine (CA) concentrations [6,11], re duces food intake |45], and decreases locomotor activity [4,7,48]. The 5-HTia receptor agonist, 8-OHDPAT [25, 37], also elevates plasma PRL [5,50] and plasma CA [8], and decreases food intake in a food deprivation paradigm [5,15].…”
mentioning
confidence: 99%
“…Although chronic imipramine treatment has been reported to decrease 5-HTr receptor binding [32,33], clomipramine is devoid of this effect [17,34], Moreover, chronic clorgyline treatment decreases 5-HTjreceptor binding [35], but did not attenuate the effect of clonidine in the present study. Furthermore, chronic imipramine treatment actually accentuates m-CPP-induced decreases in food intake and locomotor activity [36] and increases in plasma prolactin [16]. As mentioned earlier in the discussion, m-CPP decreases food intake and locomotor activity and increases plasma prolactin by stimulation of postsynaptic 5-HTic receptors.…”
Section: Discussionmentioning
confidence: 75%